Evaluating Homeopathy as an Alternative to Antibiotics for Surgical Wound Management (Journal of the Bangladesh Agricultural University, 2026)
Background and objectives: Postoperative wound management commonly relies on antibiotics and anti-inflammatory drugs; however, increasing antimicrobial resistance (AMR) has prompted interest in complementary approaches. This pilot study aimed to explore the effects of selected homeopathic remedies in postoperative wound management and to compare observed outcomes with conventional allopathic therapy in a goat surgical model. Methods: Six healthy female Black Bengal goats were randomly allocated into two groups (n=3 each): a control group receiving standard allopathic postoperative care (antibiotics, anti-inflammatory and antihistaminic drugs) and a treatment group managed with homeopathic remedies (Calendula officinalis-Q, Arnica montana-200, Hypericum perforatum-200, and Staphysagria 200). Animals underwent skin incision, laparotomy, and rumenotomy under aseptic conditions. Wound healing time, duration of acute pain, and infection status were monitored. Data were analyzed descriptively due to the small sample size. Results: All wounds healed in both groups without postoperative infection. However, the control group showed shorter mean healing times (6.7, 9.3, and 9.7 days for skin incision, laparotomy, and rumenotomy, respectively) compared to the homeopathic group (8.3, 11.7, and 15.0 days). Duration of postoperative pain was also shorter in the control group. Delayed recovery in the homeopathic group was more evident in major abdominal procedures. Conclusion: In this small exploratory study, conventional antibiotic-based postoperative management was associated with faster healing and earlier pain resolution. Homeopathic remedies supported eventual wound closure but were associated with delayed recovery, particularly in more invasive procedures. These findings suggest that such approaches may have limited or adjunctive roles rather than serving as replacements for standard therapy. Larger, controlled studies with objective outcome measures are required to validate these observations.J Bangladesh Agril Univ 24(2): 73–80, 2026